Fabrikasi slaid mikroatur cDNA lates calcaficer - Khoo, Choon Kiat; Adura Mohd-Adnan; Kua, Beng Chu; Abdul Munir Abdul Murad (Universiti Kebangsaan Malaysia, 2009)
DNA microarray technology has become an essential part of biological research. It enables the genome-scale analysis of gene expression of various model systems performed. DNA microarray performance is measured by parameters like spot density, spot characteristics (morphology, probe density and hybridised intensity), background, specificity and sensitivity. Using the GeneTac™G3 arrayer, we fabricated the Asian seabass (Lates calacrifer) cDNA microarray, comprising 1920 selected cDNAs clones sourced from spleen and liver cDNA libraries, and spotted in duplicate. Putative functions encoded by these clones include immunity, stress response, metabolism, transport, transcription and translation. Negative controls such as oligonucleotide (A)50, and several Saccharomyces cerevisiae and Escherichia coli genes as well as positive controls such as a serial dilution of L. calcarifer genomic DNA and cDNA were also spotted onto the glass slide. It was observed that the probes concentration ranging from 150-250 μg/mL and the type of positive and negative control employed produced quality slide. In addition, the overnight drying of the spotted slides and slide rehydrating produced morphologically even and round DNA spots. Slide quality controls employed demonstrated the functionality of the fabricated slides in profiling the L. calcarifer transcriptome response toward Cryptocaryon irritans infection.